2009
DOI: 10.1177/0886260509340536
|View full text |Cite
|
Sign up to set email alerts
|

Rape Myth Acceptance Among Korean College Students: The Roles of Gender, Attitudes Toward Women, and Sexual Double Standard

Abstract: The purpose of the current study was to examine factors that influence rape myths among Korean college students. This study was particularly interested in the ways in which attitudes toward women and sexual double standard affect the relationship between gender and rape myths. Although the incidence of rape is a common concern in many current societies, within each society, the specific components of rape myths reflect the cultural values and norms of that particular society. A sample of 327 college students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
1
36
0
5
Order By: Relevance
“…The actual frequency of SA is assumed to be much higher, however. A 2007 survey using a representative national sample of 13,608 Korean college students revealed that the report rate for rape and attempted rape was estimated to be only 7.1% of the actual incidence [2]. …”
Section: Introductionmentioning
confidence: 99%
“…The actual frequency of SA is assumed to be much higher, however. A 2007 survey using a representative national sample of 13,608 Korean college students revealed that the report rate for rape and attempted rape was estimated to be only 7.1% of the actual incidence [2]. …”
Section: Introductionmentioning
confidence: 99%
“…This separation from the state may lead Buddhism to have less direct influence on rape and rape myths. Admittedly, rape myths and high rates of rape are found in East Asian culture (e.g., Lee et al 2010;WHO 2005;Yamawaki 2009), but Buddhism seems to play a weaker role in creating and sustaining these myths than Christianity, Judaism, and the religions discussed here.…”
Section: Buddhismmentioning
confidence: 92%
“…Indeed, in interviews with women in Thailand, Khuankaew (2007) found that women believed that they were to blame for monks' uncontrollable sexual desires. Further, South Korean male and female college students, rating several different rape myths, most strongly endorsed rape myths that suggested rape was due to men's uncontrollable sexual desires (Lee et al 2010). Therefore, one can see the rape myths "women ask to be raped" and "he didn't mean to" emerge in misguided teachings or interpretation of Buddhism (for a review of rape myths, see Lonsway and Fitzgerald 1994).…”
Section: Buddhismmentioning
confidence: 97%
See 1 more Smart Citation
“…Terakhir, studi-studi sebelumnya cenderung mengukur bentuk kekerasan yang terbatas, khususnya pada kekerasan fisik dan seksual dan dengan demikian mengabaikan bentuk penting lain dari kekerasan terhadap istri termasuk kekerasan emosional dan ekonomi yang dibahas dalam kajian ini (Lee, BuschArmendaris, Kim and Lim, 2007;2010).…”
Section: Pendahuluanunclassified